Correlation among blood vitamin E levels, hematological parameters, and cytokine expression of peripheral blood leukocytes during the transition period in dairy cows - Li, Cheng-Yan; Ng, Jue-Sze; Chiang, Hsin-I; Chan, Jacky Peng-Wen; Wang, Chien-Kai (Italian journal of animal science, 2024)
Significant physiological changes in transition cows affect dry matter intake and immune function. Vitamin E is a vital fat-soluble vitamin for cells, influencing their signal transduction. However, limited research discusses the changes in vitamin E levels in bovine peripheral blood leukocytes (PBL) during the transition period. This study aimed to investigate changes in lipid metabolites and vitamin E levels in the blood and to observe their relation to vitamin E and inflammatory-related cytokines changes in PBL during the transition period. The non-esterified fatty acid levels peaked on the day of calving, while the β-hydroxybutyrate levels gradually rose after calving. Additionally, the circulating levels of cholesterol and vitamin E gradually increase after calving. However, the vitamin E to cholesterol ratio was lower postpartum. In PBL, vitamin E levels in peripheral blood mononuclear cells increased postpartum. Based on the Pearson correlation analysis, postpartum lipid metabolites were correlated with cytokine expression in PBL. However, none of the blood indicators were associated with PBL’s vitamin E content. Additionally, the vitamin E content of PBL showed a positive correlation with their cytokine expression. In summary, this study observed significant changes in both serum lipid metabolites and vitamin E, while the vitamin E content of PBL remained relatively stable. Moreover, the vitamin E content in PBL positively correlates with cytokine expression, suggesting that the vitamin E levels in PBL during the transition period may be involved in regulating cytokines. Therefore, the impact of PBL vitamin E levels on its function warrants further investigation.